2016
DOI: 10.1530/eje-16-0252
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic markers and response to vandetanib therapy in sporadic medullary thyroid cancer patients

Abstract: Objective: Medullary thyroid carcinoma (MTC) occurs sporadically in 75% of patients. Metastatic disease is associated with significantly poorer survival. The aim of this study was to identify prognostic markers for progressive MTC and oncogenic factors associated with response to vandetanib therapy. Design and methods: Clinical courses of 32 patients with sporadic MTC (n = 10 pN0cM0, n = 8 pN1cM0, n = 14 pN1cM1) were compared with genetic profiles of the patients' primary tumour tissue. Analysis for RET proto-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
0
16
1
Order By: Relevance
“…After reading full-texts, we further excluded 35 studies and the remaining 23 studies, comprising 964 sporadic MTCs were included for final analyses (Fig. 1) (Zedenius et al 1994, 1995, Romei et al 1996, Frisk et al 2000, Schilling et al 2001, Cho et al 2005, Dvorakova et al 2008, Elisei et al 2008, Goutas et al 2008, Moura et al 2009, Mian et al 2011, Pasquali et al 2011, Schulten et al 2011, Ciampi et al 2013, Lyra et al 2014, Simbolo et al 2014, Chuang et al 2016, Grubbs et al 2016, Nascimento et al 2016, Tiedje et al 2016, Cavedon et al 2017. The characteristics of all included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After reading full-texts, we further excluded 35 studies and the remaining 23 studies, comprising 964 sporadic MTCs were included for final analyses (Fig. 1) (Zedenius et al 1994, 1995, Romei et al 1996, Frisk et al 2000, Schilling et al 2001, Cho et al 2005, Dvorakova et al 2008, Elisei et al 2008, Goutas et al 2008, Moura et al 2009, Mian et al 2011, Pasquali et al 2011, Schulten et al 2011, Ciampi et al 2013, Lyra et al 2014, Simbolo et al 2014, Chuang et al 2016, Grubbs et al 2016, Nascimento et al 2016, Tiedje et al 2016, Cavedon et al 2017. The characteristics of all included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Pertinent data for RET mutations from 12 studies were included for analysis (Zedenius et al 1994, Schilling et al 2001, Dvorakova et al 2008, Elisei et al 2008, Moura et al 2009, Mian et al 2011, Schulten et al 2011, Simbolo et al 2014, Chuang et al 2016, Grubbs et al 2016, Nascimento et al 2016, Tiedje et al 2016). There was a statistical difference in male proportion between two groups ( Supplementary Fig.…”
Section: Male Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…Hereditary medullary thyroid carcinoma (MTC) is characterized by germline RET mutations [38] and in 40–60% of sporadic MTC somatic RET mutations are present [39, 40], which cause constitutive activation of the RET tyrosinkinase and in consequence MAPK/ERK and PI3K pathway activation. In follicular-cell derived thyroid carcinoma RET mutations are generally rare events [41].…”
Section: Discussionmentioning
confidence: 99%
“…The various types of features in this signature reveal the role of various non-coding transcripts along with protein-coding transcripts in the progression of cancer. Out of 28 protein-coding, five genes; TERT [68], FLT4 [69], DUSP6 [70], USP10 [71] and POMC [72] have already been implicated in thyroid cancer. miR-3196 has also been found to be downregulated in PTC nonmetastasized patients [73].…”
Section: Plos Onementioning
confidence: 99%